2013
DOI: 10.1080/09593330.2012.710254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of paper mill wastewater on soil properties and crop yield through lysimeter studies

Abstract: Paper and pulp industries produce large quantities of wastewater which can have adverse effects on the receiving water systems. In the present study lysimeters were used and filled with different soils replicating natural soil horizons and provided with a leachate collection system. The physico-chemical characteristics of the soil in each lysimeter and the quality of wastewater before leaching were assessed. Treated wastewater was evaluated for crop irrigation, and was categorized according to the irrigation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Another study did not find any increases in soil OC after application of the paper mill effluent (Lin et al, 2008). In contrast, an increase in OC content in an experiment carried out in lysimeters filled with soil after the application of paper mill wastewater was associated with the dissolved lignin present in the residue (Singh et al, 2013).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study did not find any increases in soil OC after application of the paper mill effluent (Lin et al, 2008). In contrast, an increase in OC content in an experiment carried out in lysimeters filled with soil after the application of paper mill wastewater was associated with the dissolved lignin present in the residue (Singh et al, 2013).…”
Section: Resultsmentioning
confidence: 91%
“…These studies focused on effluent reuse for agriculture, mainly water from treated urban and industrial sewage. A few studies assessing the use of waste from paper mill industries in soils are reported in the literature (Chhonkar et al, 2000;Singh et al, 2002;Singh, 2007;Roy et al, 2008;Boruah and Hazarika, 2010;Rezende et al, 2010;Morris et al, 2012;Singh et al, 2013). However, studies on the reuse of paper mill industry effluents and their potential use in forest soils are scarce, especially for tropical soils and for effluents resulting from the industrial Kraft bleaching process.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment compromising of fly ash 10 t ha -1 + bio sludge 6 t ha -1 had higher concentration of cations the field soil compared to column soil except for magnesium (Table 1 and 2). Roy et al (2008) and Singh et al (2013) reported increased pH value, the electrical conductivity (ECe) and exchangeable sodium percentage (ESP) in soils irrigated with waste water. The EC, organic carbon, available K, exchangeable cation (Cu 2+ and Mg 2+ ) were found to be significantly higher in treated treatments than control.…”
Section: Resultsmentioning
confidence: 99%
“…The treated industrial wastewaters can be used for secondary purposes such as agricultural needs for irrigating the crops. (Kansal, 1994) [1] The organic carbon content and available NPK in the soil were found to be increased in the waste water irrigated soils (Singh et al, 2013) [2] and improve the soil fertility. The pulp and paper industry being one of the largest consumers of fresh water releases a huge quantity of effluent which when used to irrigate crops can be an alternative source of plant nutrients.…”
Section: Introductionmentioning
confidence: 99%